Advanced power cycler with intelligent monitoring strategy of IGBT module under test. (September 2017) - Choi, U.M.; Blaabjerg, F.; Iannuzzo, F.
Abstract: Power cycling (PC) test is one of the important test methods to assess the reliability performance of power device modules related to packaging technology, in respect to temperature stress. In this paper, an advanced power cycler with a real-time V CE _ ON and V F measurement circuit for the IGBT and diode, which for the wear-out condition monitoring are presented. This advanced power cycler allows to perform power cycling test cost-effectively under conditions close to real power converter applications. In addition, an intelligent monitoring strategy for the separation of package-related wear-out failure mechanisms has been proposed. By means of the proposed method, the wear-out failure mechanisms of an IGBT module can be separated without any additional efforts during the power cycling tests. The validity and effectiveness of the proposed monitoring strategy are also verified by experiments. Highlights: Power cycling test under the condition close to real power converter applications Real-time monitoring of wear-out failure indicator of an IGBT module Separation of wear-out failure mechanisms of an IGBT module without re-characterization